R-loops and initiation of DNA replication in human cells: a missing link? - Lombraña, Rodrigo; Almeida, Ricardo; Álvarez, Alba; Gómez, María (Frontiers in Genetics, 2015)
The unanticipated widespread occurrence of stable hybrid DNA/RNA structures (R-loops) in human cells and the increasing evidence of their involvement in several human malignancies have invigorated the research on R-loop biology in recent years. Here we propose that physiological R-loop formation at CpG island promoters can contribute to DNA replication origin specification at these regions, the most efficient replication initiation sites in mammalian cells. Quite likely, this occurs by the strand-displacement reaction activating the formation of G-quadruplex structures that target the Origin Recognition Complex (ORC) in the single-stranded conformation. In agreement with this, we found that R-loops co-localize with the ORC within the same CpG island region in a significant fraction of these efficient replication origins, precisely at the position displaying the highest density of G4 motifs. This scenario builds on the connection between transcription and replication in human cells and suggests that R-loop dysregulation at CpG island promoter-origins might contribute to the phenotype of DNA replication abnormalities and loss of genome integrity detected in cancer cells.